A POSSIBLE RELATIONSHIP BETWEEN THE SETS OF QUASI-LINEAR LOCAL TRENDS STATISTICALLY DETECTED IN THE VARIATIONS OF THE MAGNETIC FIELD PARAMETERS BEFORE EARTHQUAKES IN SEISMICLY ACTIVE ZONES OF THE BLACK SEA, CAUCASUS, AND WESTERN ASIA - A. E. Volvach; L. P. Kogan; K. H. Kanonidi; L. I. Nadezhka; I. T. Bubukin; O. V. Boborikina; V. B. Shtenberg; L. N. Volvach; D. T. Biazitov (Геодинамика и тектонофизика)
The paper considers the properties of statistical function whose plot comprises a set of measurements of H-component of the magnetic field. There has been found a set of quasi-linear objects with very similar parameters. In the context of a hypothesis about the correspondence of these structures to seismic processes, there has been made an estimate of time intervals typical for the phases of decrease and increase in the level of compression of lithospheric plate material in the earthquake source zones. It has been shown that the application of statistical methods in geophysics may contribute to near real-time assessment of seismic hazard in the study area.